THE WORLD DANCES - Valijonova Sugdiyona (Antis Publisher, 2024)
This article presents interesting facts about the emergence of world folk dances, their stages of development, types of dances popular in the XVIII-XIX centuries, including: “Tarantella”, “Farandola”, “Waltz”, “Mazurka”, “Polonez”, “Bal”, “Branl”, methods of their performance, originality and musical dimensions of dance movements, as well as some folk dances that are now forgotten.